2018
DOI: 10.5194/acp-18-5455-2018
|View full text |Cite
|
Sign up to set email alerts
|

Studying volatility from composition, dilution, and heating measurements of secondary organic aerosols formed during <i>α</i>-pinene ozonolysis

Abstract: Abstract. Traditional yield curve analysis shows that semi-volatile organic compounds are a major component of secondary organic aerosols (SOAs). We investigated the volatility distribution of SOAs from α-pinene ozonolysis using positive electrospray ionization mass analysis and dilution- and heat-induced evaporation measurements. Laboratory chamber experiments were conducted on α-pinene ozonolysis, in the presence and absence of OH scavengers. Among these, we identified not only semi-volatile products, but al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(62 citation statements)
references
References 43 publications
(80 reference statements)
6
56
0
Order By: Relevance
“…As a result, a OFR fate correction for S/IVOCs is not feasible. Previous field measurements and laboratory studies demonstrated that SOA from various sources were mainly ~40%-80% L/ELVOCs and ~20%-60% S/IVOCs (Hong et al, 2017;Saha et al, 2017;D'Ambro et al, 2018;Sato et al, 2018;Saha et al, 2018). In our experiments, the low-NOx yields are significantly higher than the high-NOx yields (paper in preparation), indicating a lower volatility for SOA formed under low-NOx conditions.…”
supporting
confidence: 48%
“…As a result, a OFR fate correction for S/IVOCs is not feasible. Previous field measurements and laboratory studies demonstrated that SOA from various sources were mainly ~40%-80% L/ELVOCs and ~20%-60% S/IVOCs (Hong et al, 2017;Saha et al, 2017;D'Ambro et al, 2018;Sato et al, 2018;Saha et al, 2018). In our experiments, the low-NOx yields are significantly higher than the high-NOx yields (paper in preparation), indicating a lower volatility for SOA formed under low-NOx conditions.…”
supporting
confidence: 48%
“…Data availability. All data used in this work can be found on the Figshare database (https://doi.org/10.6084/m9.figshare.10026131; Sato et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Chemical composition analysis of the Teflon filter samples was conducted using electrospray ionization liquidchromatography time-of-flight mass spectrometry (LC-TOF-MS) (Agilent Technologies, UK) similarly as in previous studies (Sato et al, 2018(Sato et al, , 2019 except that negative-mode was used in this study whereas positive-mode was used in those previous 150 studies. The mass calibration and lock-mass correction were conducted using G1969-85000 and G1969-85001 tuning mixtures (Agilent Technologies, UK), respectively.…”
Section: Lc-tof-ms Analysismentioning
confidence: 99%
“…where mSOA was calculated assuming SOA density of 1.34 g cm −3 (Sato et al, 2018) and equal to the arithmetic mean of the last three data of each experimental run. It was corrected for wall loss using the bulk-volume wall-loss rate, assuming a firstorder wall-loss constant which is independent of particle size and reaction time (Pathak et al, 2007b).…”
Section: Wall-loss Experimentsmentioning
confidence: 99%
See 1 more Smart Citation